2013
DOI: 10.14442/generalist.36.23
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of medical records and prescription data from long-term disaster medical support following the subacute phase of the Great East Japan Earthquake on March 11, 2011

Abstract: ある.また支援の介入が早いほど,急性疾患と慢性疾患の両方の治療薬を災害医療支援チームは必要とする. AbstractIntroduction:There are few reports of long-term medical support activities in disaster areas. We analyzed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Shiba et al [11] determined the number of patients and pharmaceutical prescriptions from medical records and prescriptions obtained during mobile medical visits during the Great East Japan Earthquake to clarify the actual circumstances of long-term disaster medical support. The results showed that the number of patients decreased from a peak of 166 patient/day at one week after the start of support on 26 March, with 24 patients/day after 11 April.…”
Section: Research On Pharmaceutical Supply and Demand During Disastersmentioning
confidence: 99%
“…Shiba et al [11] determined the number of patients and pharmaceutical prescriptions from medical records and prescriptions obtained during mobile medical visits during the Great East Japan Earthquake to clarify the actual circumstances of long-term disaster medical support. The results showed that the number of patients decreased from a peak of 166 patient/day at one week after the start of support on 26 March, with 24 patients/day after 11 April.…”
Section: Research On Pharmaceutical Supply and Demand During Disastersmentioning
confidence: 99%
“…In order to calculate this variation v, the corrected for pressure data of a reference station S are used [5]. The reference station should have similar rigidity to the main station in order to assume that they both have similar cosmic ray spectra.…”
Section: Barometric Coefficient Calculationmentioning
confidence: 99%